Higher Education in Africa: Facing the Challenges in the 21st Century - Mohamedbhai, Goolam (International Higher Education, 2011)
The article discusses some of the daunting challenges currently facing higher education in Africa, such as student enrollment, funding, research and quality assurance. It emphasises that successfully addressing these challenges requires multiple approaches at institutional, national and regional levels, and needs commitment and collaboration of all stakeholders.